Cellulose, Cellobiose, and Glucose Cause Similar Decreases to Molar Conductivity and Drastically Different Increases to Dynamic Viscosity of 1-Ethyl-3-Methylimidazoilum Acetate Based Solvents. (23rd July 2018) - Fahey, Patrick J.; Durkin, David P.; Fox, Eric T.; Gobet, Mallory; Greenbaum, Steven; De Long, Hugh C.; Trulove, Paul C.
Abstract : The effect of dissolved cellulose, cellobiose, and glucose on ionic conductivity, density, and viscosity were evaluated for 1-ethyl-3-methylimidazolium acetate (EMIAc) and 1:1-mole-ratio mixtures of EMIAc with acetonitrile (1:1 EMIAc:AN) and water (1:1 EMIAc:H2 O). Test solutions were made with these three solvents by dissolving 0.1, 0.5, 1.0, and 3.0 wt.-% of either cotton, microcrystalline cellulose (MCC), cellobiose, or glucose. Each solute caused slight decreases in ion conductivity at higher solute contents, decreasing to factors only as low as 0.7 of their corresponding solvent-type's conductivity. The solutes' effects upon viscosity differed: cellulose solutes caused increases in viscosity upon reaching higher solute contents, where the solvents' viscosities increased to factors between 10 and 20 at 3.0 wt.-% MCC and to factors between 40 and 140 at 1.0 wt.-% cotton. This difference in impact on viscosity between MCC and cotton is possibly due to cotton's higher degree of polymerization. Meanwhile cellobiose and glucose only increased viscosity to factors as high as 1.1 and 1.3, respectively, upon reaching 3.0 wt.-% solute contents. The large increases in viscosity and corresponding small decreases in conductivity make the solutions of 3.0 wt.-% MCC and 0.5 and 1.0 wt.-% cotton appear superionic.